EVALUATION OF TEACHING SKILL PRACTICE PROGRAMS, IN THE STATE UNIVERSITY EDUCATION DEVELOPMENT INSTITUTION JAKARTA - Bambang Afriadi; Agus Dudung (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2021)
The purpose of this study is to describe the Program Practice Skills Teaching (PKM/ Praktik Keterampilan Mengajar) in semester 106, at the Educational Development Institute State University of Jakarta. The evaluation model used in this study is a formative and summative evaluation model developed by Michele Shriven. Formative evaluation is carried out during the program to provide information to the program leader as program improvement materials. While the summative evaluation is done at the end of the program. This research use evaluation analysis with qualitative and quantitative approach. How to collect data on this evaluation research is using techniques observation, questionnaires, interviews, and documentation. The results showed that in the formative evaluation, it can be seen that in general the process of Program PKM was by existing guidelines. So can be maintained the existence of the PKM Program. While the results of the summative evaluation showed that the PKM Program, in the high category, is based on the value of the minimum PKM Program participants B provided by the teacher mentor and lecturer mentor of the final exam.